2018
DOI: 10.15560/14.3.579
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of tetraodontiform fishes of the Andaman and Nicobar Islands, India

Abstract: Some fish groups are common on coral reefs, but we still lack fundamental information about how fish assemblages vary across seascapes. The order Tetraodontiformes, which includes pufferfish, triggerfish, shingles, porcupinefish, burrfish, leatherjacketfish, filefish, and trunkfish, is one such group. We systematically surveyed 75 sites around 52 islands of the Andaman and Nicobar archipelago to evaluate the occurrence and distribution of tetraodontiform fishes. We recorded 25 species from 16 genera and 6 fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The average relative gut length (RGL) of Odonus niger in this study indicated this species to be omnivorous, which is in agreement with the previous report of Patankar et al (2018), wherein they recorded omnivorous type of feeding habit in various balistids (Balistapus undulatus, Melichthys indicus, Pseudobalistes fuscus, Rhinecanthus aculeatus, Sufflamen bursa and Sufflamen chrysopterus). Omnivorous feeding habits were also documented in Balistes vetula (Randall, 1967), Melichthys niger (Hobson, 1974) and Parikas caber (Russell, 1983).…”
Section: Food and Feedingsupporting
confidence: 92%
“…The average relative gut length (RGL) of Odonus niger in this study indicated this species to be omnivorous, which is in agreement with the previous report of Patankar et al (2018), wherein they recorded omnivorous type of feeding habit in various balistids (Balistapus undulatus, Melichthys indicus, Pseudobalistes fuscus, Rhinecanthus aculeatus, Sufflamen bursa and Sufflamen chrysopterus). Omnivorous feeding habits were also documented in Balistes vetula (Randall, 1967), Melichthys niger (Hobson, 1974) and Parikas caber (Russell, 1983).…”
Section: Food and Feedingsupporting
confidence: 92%
“…The species richness of tetraodontids reported in this study is higher than in other regions of Brazil and the world. Off the south‐east coast of Brazil, Menezes () recorded 25 species of Tetraodontiformes, while Willems, Backer, Mol, and Vincx () reported six species in Suriname, Bilecenoğlu, Taşkavak, Mater, and Kaya () found 18 species in Turkey, Patankar et al () reported 25 species in India, and Carneiro, Martins, Landi, and Costa () recorded 28 species in Portugal.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 437 valid species of Tetraodontiformes, distributed in 10 families and inhabiting all oceans, estuarine zones, and fresh waters are recognized (Fricke, Eschmeyer, & Van der Laan, ; Monteiro‐Neto et al, ). More than half of Tetraodontiformes species are notable components of coral reefs and seagrass ecosystems, where they play functional roles of herbivores, macroinvertivores, piscivores, zooplanktivores and corallivores (Matsuura, ; Patankar, Paranjape, Tyabji, Wagh, & Marathe, ; Stump, Ralph, Comeros‐Raynal, Matsuura, & Carpenter, ). By feeding on multiple trophic groups and/or integrating the diet of other fishes, Tetraodontiformes also indirectly influence the structure and composition of their habitats (Darling et al, ; Patankar et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maj ority of these fishes are vital components of coral reefs and seagrass ecosystems and play functional roles of herbivores, macroinvertivores, piscivores, zooplanktivores, and corallivores (Matsuura, 2015;Stump et al, 2018;Eduardo et al, 2020). They have been reported to influence the trophic structure and composition of their habitats by feeding on multiple trophic groups and/or integrating the diet of other fishes (Darling et al, 2017;Patankar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%